The gematrical numbers in dimensions of the "Melencolia I" engraving - Tine Kurent (Acta Neophilologica, 1998)
The Melancholy engraving by Dürer and Agrippa is hiding its gematrical messages not only in the numbers of its magic square but also in the numbers forming its modular dimensions. If the sphere on the lower left side of the composition is 10 modules in diameter, the magic square measures 8 by 8 modules, and the print is 70 by 55 modules large. The circumference of the etching equals 250 and its diagonal 89 modules. In the numbers 55, 70, 250 and 89 are hidden gematrical messages, prayers, cursing, the name of the Melancholia itself and the names of its authors.